2000
DOI: 10.1103/physrevb.61.11649
|View full text |Cite
|
Sign up to set email alerts
|

Two rapid oscillations in the magnetoresistance in the field-induced spin-density-wave state of(TMTSF)2ClO4

Abstract: We report a systematic study of longitudinal and transverse magnetoresistance in the quasi-one-dimensional organic conductor (TMTSF) 2 ClO 4 . We found two distinctly different quantum ͑rapid͒ oscillations ͑RO's͒ at different temperature regions in the field-induced spin-density-wave ͑FISDW͒ phase. For temperature sweeps in a fixed field, a resistance peak is observed at T* which depends on the field. Surprisingly, the type of RO is correlated with T*(H). The difference between two oscillations leads us to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 28 publications
5
22
1
Order By: Relevance
“…͓Note that V c1 ϭ0 if t 2b is large enough.͔ Two successive transitions have been observed in (TMTSF) 2 ClO 4 at high magnetic field. [6][7][8] The possibility that each of these transitions corresponds to an intraband pairing, thus partially destroying the Fermi surface, has been suggested early on. 6 Although our conclusions do not apply stricto sensus to the experimental situation, since they are restricted to the zero-field case, they indicate that this scenario could indeed take place in (TMTSF) 2 ClO 4 at high field, in agreement with the conclusions of Refs.…”
Section: Discussionmentioning
confidence: 99%
“…͓Note that V c1 ϭ0 if t 2b is large enough.͔ Two successive transitions have been observed in (TMTSF) 2 ClO 4 at high magnetic field. [6][7][8] The possibility that each of these transitions corresponds to an intraband pairing, thus partially destroying the Fermi surface, has been suggested early on. 6 Although our conclusions do not apply stricto sensus to the experimental situation, since they are restricted to the zero-field case, they indicate that this scenario could indeed take place in (TMTSF) 2 ClO 4 at high field, in agreement with the conclusions of Refs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Moser et al 19 have carried out magnetoresistance measurements up to 23 T and gave evidence for a crossover line between 17 T and 19 T, which appears as an extension of the 3.5 K phase boundary of McKernan et al Such extension has been confirmed by Chung et al 20 who concluded, based on magnetoresistance studies between 8 and 20 T, that the phase diagram shows more than two different subphases inside the main FISDW phase of the ClO 4 salt. Figure 1 presents a generic temperature-magnetic field phase diagram where we summarize the different experimental results cited above.…”
Section: A Experimental Resultsmentioning
confidence: 83%
“…The predicted oscillations disagree with experiments, which have not given evidence of any oscillating phase boundary in the high field states. 13,15 Furthermore, the small V models 22,23,25 fail to explain the recently obtained experimental results, in particular, the presence of the first-order transition line at 3.5 K. 16,19,20 This failure has been thought to be due to the perturbation theory used to deal with the anion gap V. 28 Therefore, nonperturbative models have been proposed.…”
Section: Small V Modelsmentioning
confidence: 99%
See 2 more Smart Citations